1996
DOI: 10.1099/00207713-46-4-859
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenesis of Relapsing Fever Borrelia spp.

Abstract: The phylogenetic relationships of 20 relapsing fever (RF) Borrelia spp. were estimated on the basis of the sequences of rrs genes. Complete sequences were aligned and compared with previously published sequences, and the similarity values were found to be 97.7 to 99.9%. Phylogenetic trees were constructed by using the three neighbor-joining, maximum-parsimony, and maximum-likelihood methods. The results of the comparative phylogenetic analysis divided the RF Borrelia spp. into three major clusters. One cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
1
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(68 citation statements)
references
References 3 publications
4
60
1
3
Order By: Relevance
“…duttonii and B . recurrentis ; this finding was also reported previously ( 12 ). Ras et al concluded that this small difference did not support these being single species but instead postulated that B .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…duttonii and B . recurrentis ; this finding was also reported previously ( 12 ). Ras et al concluded that this small difference did not support these being single species but instead postulated that B .…”
Section: Discussionsupporting
confidence: 91%
“…recurrentis , and B. crocidurae ; however, a small number of nucleotides differentiated these clusters. Some Old World relapsing fever spirochetes show a high degree of similarity, both in using 16S RNA gene sequences ( 12 ) and in flagellin ( 20 , 24 ). Using the 16S RNA gene, we found that only 4 bases differed over the rr s gene between B .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human infection with B. crocidurae appears to be more prevalent than previously described, however ( 14 ). This increase could be attributed to improved diagnostic capabilities and sample processing ( 15 ), but it is largely due to molecular techniques that can facilitate not only detection but also subsequent identification through sequencing the target gene ( 16 , 17 ). …”
Section: Tickborne Relapsing Feversmentioning
confidence: 99%